Effects of organic loading rate on biogas production from macroalgae: Performance and microbial community structure. (July 2017) - Sun, Meng-Ting; Fan, Xiao-Lei; Zhao, Xiao-Xian; Fu, Shan-Fei; He, Shuai; Manasa, M.R.K.; Guo, Rong-Bo
Highlights: Effects of organic loading rate on anaerobic digestion of macroalgae were studied. The growing organic loading rate in an appropriate range could improve biogas yield. The overrange organic loading rate could cause system instability. Unfavorable VFAs concentration, pH and salinity might be main causes for instability. Several bacterial and archaeal phyla altered with growing OLR apparently. Abstract: Macroalgae biomass has been considered as a promising feedstock for biogas production. In order to improve the efficiency of anaerobic digestion (AD) of macroalgae, semi-continuous fermentation was conducted to examine the effects of organic loading rate (OLR) on biogas production from Macrocystis pyrifer . Results showed that, under OLRs of 1.37, 2.74, 4.12 and 6.85 kg VSsubstrate /(m 3 ·d), the average unit biogas yields were 438.9, 477.3, 480.1 and 188.7 mL/(g VSsubstrate d), respectively. It indicated that biogas production was promoted by the increased OLR in an appropriate range while inhibited by the OLR beyond the appropriate range. The investigation on physical-chemical parameters revealed that unfavorable VFAs concentration, pH and salinity might be the main causes for system failure due to the overrange OLR, while the total phenols failed to reach the inhibitory concentration. Microbial community analysis demonstrated that several bacterial and archaeal phyla altered with increase in OLR apparently.